2004
DOI: 10.1159/000075568
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Male Hemodialysis Patients

Abstract: Background: Health-related quality of life (QOL) is affected in hemodialysis patients (HD). A number of factors such as age, anemia, and comorbidity had been implicated in decreased QOL. Erectile dysfunction (ED) is a frequent and potentially treatable complication in HD patients. In this cross-sectional study, we aimed to evaluate the possible relation between the QOL and ED in HD patients. Patients and Methods: Among the 511 chronic HD patients dialyzed in 11 outpatient HD centers, 148 male patients (mean ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 9 publications
3
60
1
2
Order By: Relevance
“…Improvement of ED is associated with marked improvement in depressive symptoms and QOL assessments. [2,[18][19][20] Guan et al showed that anemia, depression, and use of beta blocker were risk factors for decreased libido in female patients with chronic renal insufficiency. In this study, the main manifestations of SD in female patients were "decreased libido, lack of orgasm and no feeling of sex pleasure."…”
Section: Discussionmentioning
confidence: 99%
“…Improvement of ED is associated with marked improvement in depressive symptoms and QOL assessments. [2,[18][19][20] Guan et al showed that anemia, depression, and use of beta blocker were risk factors for decreased libido in female patients with chronic renal insufficiency. In this study, the main manifestations of SD in female patients were "decreased libido, lack of orgasm and no feeling of sex pleasure."…”
Section: Discussionmentioning
confidence: 99%
“…Sexual dysfunction in Chinese rural women JTF Lau et al 18,19 Only 38.7% of the respondents were satisfied with their sexual life, while 64.0% of the respondents stated that sexual life was not important to them. Sexual well-being may therefore have been under-emphasized by females in rural China.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that worsening of the quality of life, especially in physical and psychological areas, increases mortality and hospitalization rates in patients with ESRD, which in turn further increases the importance of quality of life in this group (11,12,13). Studies examining the factors affecting the quality of life have started to increase in recent years, and particularly, SD and anxiety and depression symptoms are suggested to be important variables affecting the quality of life (2,14,15,16,17,18,19,20). Peng et al (21) reported that advanced age, diabetes, and depressive symptoms are independently related to SD and that the quality of life of patients with SD is lower.…”
Section: Introductionmentioning
confidence: 99%